Carminda Cavaco: pioneer of tourism studies in Portugal - Sarmento, João Carlos Vicente (2016)
[Extrato] On a cold and misty winter morning we were warmly greeted by Carminda Cavaco on her Lisbon apartment. Serenely on her couch, lighting a cigarette at regular intervals, Carminda happily answered our endless questions and calmly (re)counted various episodes of her life. We chatted for about three hours, scribbling some notes hastily, and travelled to her youth, to her voyages and initial papers, to the development of her early career, attempting to understand the paths that brought her to become the pioneer and the most influential Portuguese academic in the field of tourism. Some weeks earlier, from the other end of the Mediterranean, Metin Kozak approached us to write her portrait, an idea to which we were immediately attracted.